Older Migrants and Overcoming Employment Barriers: Does Community Activism Provide the Answer? - Flynn, Matt; Wong, Louise (Frontiers in Sociology, 2022)
As populations age and pension ages rise, there is a growing interest in the ability of workers to extend working life. In response to a call for a more robust dialogue on the heterogeneity of the older workforce, this article explores the interplay between different employment barriers faced by one group facing significant employment barriers: older migrants. Older Chinese migrants in the United Kingdom face multiple barriers to work resulting from age, ethnicity and the intersectionality of such barriers which creates a unique set of barriers to continued work. Community activism can play an important role in supporting older constituents, particularly in matching the skills which they have to offer with the needs within and beyond the migrant community. In this study, we use Participatory Action Research to explore with older Chinese migrants the barriers they face in the job market and how community activism can empower them in maintaining employment. As government seeks to raise real retirement ages, more research is needed on its implications for vulnerable groups of older people including migrants.